PENGEMBANGAN SUMBER DAYA MANUSIA DI KANTOR NOTARIS DAN PPAT HOBBBY SIMANUNGKALIT SINTANG : Motivasi kerja, Pendidikan dan Pelatihan, Disiplin Kerja - Abang Zainudin (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2024)
Human resource development plays an important role in improving organizational performance in order to remain professional in carrying out their duties. Conceptually, employees are the organization's human resources, which need attention. Notary offices have an important role in Indonesia, which is a state of law. One of them is to serve the public in terms of making authentic deeds as evidence or as a legal or absolute requirement for certain legal acts. Notary employee resource development is an internal issue concerning capacity at the individual level, organizational level, and sustainable system level. The development of employee resources at the Notary Office of Hobby Simanungkalit Sintang is inseparable from the role of notary duties in order to foster employees in working to achieve good performance. Employee resource development at the Notary Office of Hobby Simanungkalit Sintang is carried out by providing motivation, enforcing discipline and including employees in education and training activities with the aim of improving employee performance.